The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/smll.202305693
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Uptake, Transfer, and Transport of Dextran‐Based Nanoparticles in Plants for Multidimensional Enhancement of Pesticide Utilization

Qiuyu Xiong,
Wenlong Liang,
Wenxuan Shang
et al.

Abstract: The development of effective multifunctional nano‐delivery approaches for pesticide absorption remains a challenge. Here, a dextran‐based pesticide delivery system (MBD) is constructed to deliver tebuconazole for multidimensionally enhancing its effective utilization on tomato plants. Spherical MBD nanoparticles are obtained through two‐step esterification of dextran, followed by tebuconazole loading using the Michael addition reaction. Confocal laser scanning microscopy shows that fluorescein isothiocyanate‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…showed that dextran NPs were mainly transported by vascular bundles in tomato, which is similar to the findings of our study. 50 These results suggested that the TF@Fe-MOF-PT NPs were capable of bidirectional transport within the rice plants and could be absorbed by the rice plants efficiently and transported to other sites within 48 h, either when applied to the roots or leaves. In conclusion, the TF@Fe-MOF-PT NPs were mainly transported upward from the roots through the xylem and phloem of the vascular system.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…showed that dextran NPs were mainly transported by vascular bundles in tomato, which is similar to the findings of our study. 50 These results suggested that the TF@Fe-MOF-PT NPs were capable of bidirectional transport within the rice plants and could be absorbed by the rice plants efficiently and transported to other sites within 48 h, either when applied to the roots or leaves. In conclusion, the TF@Fe-MOF-PT NPs were mainly transported upward from the roots through the xylem and phloem of the vascular system.…”
Section: Resultsmentioning
confidence: 75%
“…In addition to the foliar attachment capacity, the ability of the plant to take up the pesticide and translocate it to the target site directly determines the effectiveness of root or foliar application, depending on the pesticide characteristics, type and scale of the carrier, plant species and growth conditions, and environmental factors. 50 To determine the uptake and translocation of TF@Fe-MOF-PT NPs in rice, rice plants were treated with FITC-labeled TF@Fe-MOF-PT NPs and observed under a confocal microscope. Hydroponics confirmed that the TF@Fe-MOF-PT NPs were transferred to rice stems and leaves via the roots, and leaf treatment confirmed that the TF@Fe-MOF-PT NPs were transferred to the rice stems and roots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation